Professional Development Strategies in the Narrative of Nepali Teacher - Kapar, Hiralal (Lumbini Journal of Language and Literature, 2022)
This paper explored the stories of four Nepali secondary level English teachers adopting strategies for their professional development under the guidance of narrative inquiry along with interview as data collection tools. Their sharing was taken as the core information for the study. Findings suggest that teachers update their knowledge in order to be familiar with new trends of English language teaching from workshop, seminar, action research, teachers’ support group and conferences. Apart from these, online courses have also given an ample opportunity to foster professionalism. Teachers impart their knowledge in classroom with students and they develop their professionalism.